Efektivitas Penggunaan Ventilator Dalam Memperpanjang Hidup Pasien Menurut Pandangan Islam - Syifa Anisa; Arvi Aliviani; Athifah Aulia; Elsa Vita; Fatmaghita Setyoningrum; Karina Gayatri; Tedi Supriyadi; Akhmad Faozi (Jurnal Kesehatan Holistic, 2026)
The use of ventilators in modern medicine often raises ethical dilemmas for Muslim families, especially when this technology is no longer capable of restoring consciousness in patients with permanent brain damage. This situation confronts the obligation to preserve life (Hifz an-Nafs) with the prohibition of futile actions (tabzir) and the principle of avoiding harm (la darar wa la dirar). Objective: This study examines the effectiveness of ventilators in depth by integrating medical data and Islamic legal norms to determine the boundary between human efforts and acceptance of Allah's will. Methods: This qualitative case study involved semi-structured interviews with medical personnel (nurses and lecturers) and religious scholars to gain a comprehensive perspective. Results: The findings indicate that ventilators are effective as a "bridge to healing" in acute cases such as pneumonia or post-surgery. However, in terminal conditions or brainstem death, these devices only serve to maintain biological markers without any functional benefit. Therefore, from an Islamic perspective, their discontinuation is permissible for the sake of the patient. Conclusion: Ventilator success is measured not only by biological lifespan, but also by the quality of life and tangible benefits it provides to patients.